Analisis Partisipasi Pemerintah Desa Dalam Perencanaan dan Pengembangan Bumdes di Desa Sumberkalong Kecamatan Kalisat Kabupaten Jember - Nita Elvita; Ririn Isnadewi; Rina Dwi Cahyati; Betty Dasilva; Prillinaya Yudhistira; Oryza Ardhiarisca (CV Muara Edukasi, 2025)
Village development is part of national development that aims to improve the welfare of the community. One of the efforts to achieve this is through the establishment of Village-Owned Enterprises (BUMDes) as a forum for the independent management of local economic potential. In this process, the village government has an important role in the planning and development of BUMDes, starting from the formulation of vision and mission, identification of business potential, to the implementation of village economic programs. Careful planning and sustainable development are key to ensuring that BUMDes can promote economic independence and increase community income. The support, commitment, and ability of the village government to manage and involve the community are crucial to the success of BUMDes as a driving force for village development